Cianamida cálcica como fertilizante nitrogenado no cultivo protegido de tomateiro e pimentoeiro - Rosa, Jessica Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
A nutrição adequada é fundamental para maximizar a qualidade e a produtividade das culturas, influenciando diretamente o uso eficiente de fertilizantes e defensivos agrícolas. A cianamida cálcica, um fertilizante composto por 18% de N e 26% de Ca, é uma fonte de liberação lenta de N no solo, com efeito inibidor da nitrificação, além de ação herbicida, fungicida e efeito colateral bactericida, sem acidificar o solo, figura com alterativa para a agricultura brasileira, em especial as Solanáceas, como o tomateiro (Solanum lycopersicum L.) e pimentoeiro (Capsicum annum L), objetos deste estudo. Assim, o objetivo com este trabalho foi avaliar o efeito do fertilizante cianamida cálcica, como fonte de N, no cultivo do tomateiro e do pimentoeiro, e definir a dose mais adequada deste para estas culturas. Os experimentos foram conduzidos em cultivo protegido, em Botucatu, SP. Os tratamentos foram as doses de 0, 200, 350, 500 e 1000 Kg ha⁻¹ de cianamida cálcica, antes do plantio. O solo foi incubado de 6 a 28 dias, em função do tratamento. Foi utilizado delineamento em blocos ao acaso com cinco repetições, compostas por dois vasos. Foram analisados altura da planta, massa fresca e seca da parte aérea e dos frutos, bem como número de frutos, teor e acúmulo dos nutrientes na parte aérea e dos frutos. As doses de cianamida cálcica, no tomateiro, influenciaram o número de cachos, teor de Mg e Mn na parte aérea, teor de N, K, B, Cu e Mn nos frutos e acúmulo de B, Cu e Mn nos frutos. Para o pimentoeiro, a houve efeito significativo das doses de cianamida de cálcio para massa fresca de frutos comerciais e total, massa seca de frutos, teor de Mg e Mn na parte aérea, acúmulo de Mn na parte aérea, teor de N, K, Cu e Zn nos fruto, por fim, acúmulo de todos os nutrientes nos frutos, exceto o S. Para o tomateiro, a dose de 350 Kg ha⁻¹ de cianamida proporcionou maior aumento na produção com relação ao controle (8%), e para o pimentoeiro a dose foi de 200 kg ha⁻¹ de cianamida, com aumento de 24% em relação ao controle.

Adequate nutrition is essential for maximizing the quality and productivity of these crops, directly influencing the efficient use of fertilizers and pesticides. Calcium cyanamide, a fertilizer composed of 18% nitrogen (N) and 26% calcium (Ca), serves as a slow-release source of N in the soil and has a nitrification-inhibiting effect, along with herbicidal, fungicidal, and bactericidal properties, without acidifying the soil. It is an alternative for Brazilian agriculture, particularly for Solanaceae such as tomato (Solanum lycopersicum L.) and bell pepper (Capsicum annuum L.), which are the subjects of this study. The aim of this study was to evaluate the effect of calcium cyanamide fertilizer, as a source of N, on the cultivation of tomato and bell pepper plants, and to determine the most appropriate doses for these crops. The experiments were conducted under protected cultivation in Botucatu, SP. The treatments included doses of 0, 200, 350, 500, and 1000 kg ha⁻¹ of calcium cyanamide applied before planting. The soil was incubated for 6 to 28 days, depending on the treatment. A randomized block design was employed with five replications, each consisting of two pots.Plant height, fresh and dry mass of the aerial parts and fruits were analyzed, as well as the number of fruits, nutrient content, and accumulation in the aerial parts and fruits. The doses of calcium cyanamide in tomato plants influenced the number of bunches, the content of magnesium (Mg) and manganese (Mn) in the aerial parts, the content of nitrogen (N), potassium (K), boron (B), copper (Cu), and manganese (Mn) in the fruits, as well as the accumulation of B, Cu, and Mn in the fruits. For bell peppers, there was a significant effect of the calcium cyanamide doses on the fresh mass of commercial and total fruits, the dry mass of fruits, the content of Mg and Mn in the aerial parts, the accumulation of Mn in the aerial parts, the content of N, K, Cu, and zinc (Zn) in the fruits, and the accumulation of all nutrients in the fruits, except sulfur (S).For tomato plants, the dose of 350 kg ha⁻¹ resulted in the greatest increase in production compared to the control (8%), while for bell pepper plants, the optimal dose was 200 kg ha⁻¹ of calcium cyanamide, leading to a 24% increase compared to the control.
Calcium cyanamide as a nitrogen fertilizer in the protected cultivation of tomato and pepper
Keywords: Solanum lycopersicum L; Capsicum annum L; Nitrogênio; Cálcio; Cianamida cálcica; Nitrogen; Calcium; Calcium cyanamide